Impact of the announcement and implementation of the UK Soft Drinks Industry Levy on sugar content, price, product size and number of available soft drinks in the UK, 2015-19: controlled interrupted time series analysis - Scarborough, P; Harrington, R (University of Oxford, 2019)
These datasets are anonymised versions of the analysis datasets for an evaluation of the impact of the UK Soft Drink Industry Levy on sugar levels, price, product size and product diversity. This study was funded by the NIHR (award numbers 16/49/01 and 16/130/01) and is supported by the NIHR Biomedical Research Centre at Oxford. Background: Dietary sugar, especially in liquid form, increases risk of dental caries, adiposity and type 2 diabetes. The UK Soft Drinks Industry Levy (SDIL) was announced in March 2016 and implemented in April 2018 and charges manufacturers and importers at £0.24 per litre for drinks with over 8g sugar per 100ml (high levy category), £0.18 per litre for drinks with 5 to 8g sugar per 100ml (low levy category) and no charge for drinks with less than 5g sugar per 100ml (no levy category). Fruit juices and milk-based drinks are exempt. We measured the impact of the SDIL on price, product size, number of soft drinks on the marketplace, and the proportion of drinks over the lower levy threshold of 5g sugar per 100ml. Methods and Findings: We analysed data on a total of 209,637 observations of soft drinks over 85 time points between September 2015 and February 2019, collected from the websites of the leading supermarkets in the UK. The dataset was structured as a repeat cross-sectional study. We used controlled interrupted time series to assess the impact of the SDIL on changes in level and slope for the four outcome variables. Equivalent models were run for potentially levy-eligible drink categories (‘intervention’ drinks) and levy-exempt fruit juices and milk-based drinks (‘control’ drinks). Observed results were compared with counterfactual scenarios based on extrapolation of pre-SDIL trends. We found that in February 2019, the proportion of intervention drinks over the lower levy sugar threshold had fallen by 33.8 percentage points (95% confidence intervals: 33.3, 34.4, p < 0.001). The price of intervention drinks in the high levy category had risen by £0.075 (£0.037, £0.115, p < 0.001) per litre – a 31% pass through rate – whilst prices of intervention drinks in the low levy category and no levy category had fallen and risen by smaller amounts, respectively. The SDIL was associated with a small impact on product size of intervention drinks and no impact on the number of drinks in supermarkets. There were sizeable differences in outcomes for branded and own-brand drinks. Equivalent models for control drinks provided little evidence of impact of the SDIL (p>0.05 for all model coefficients). These results are not sales weighted, so do not give an account of how sugar consumption from drinks may have changed over the time period. Conclusions: The results suggest that the SDIL incentivised many manufacturers to reduce sugar in soft drinks. Some of the cost of the levy to manufacturers and importers was passed on to consumers as higher prices, but not always on targeted drinks. These changes could reduce population exposure to liquid sugars and associated health risks. Registration: ISRCTN 18042742